1990
DOI: 10.1254/jjp.52.307
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of OKY-046 on spasmogen-induced bronchoconstrictions in sensitized and non-sensitized guinea pigs.

Abstract: Abstract-We examined the effect of thromboxane A2 (TXA2) synthetase inhibitor, OKY-046, on bronchoconstriction induced by antigen and various spasmogenic mediators in guinea pigs in vivo. Further, inhibitory activities of OKY-046 on contractions of isolated tracheae and lung parenchymal strips induced by various contractile agents were also investigated in vitro. OKY-046, but not indomethacin, significantly inhibited antigen-induced bronchoconstriction in a dose-dependent manner. Moreover, OKY-046 attenuated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…It has been reported that TXA2 contributes to the bronchoconstriction induced by intravenous administra tion of peptide LTs (18,(22)(23)(24)(25)(26). In the present study, bronchoconstriction induced by LTC4 (2 ,ug/kg) or LTD4 (2,ug/kg) was blocked only at the initial phase by indomethacin as a cyclooxygenase inhibitor.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It has been reported that TXA2 contributes to the bronchoconstriction induced by intravenous administra tion of peptide LTs (18,(22)(23)(24)(25)(26). In the present study, bronchoconstriction induced by LTC4 (2 ,ug/kg) or LTD4 (2,ug/kg) was blocked only at the initial phase by indomethacin as a cyclooxygenase inhibitor.…”
Section: Discussionsupporting
confidence: 50%
“…Among the reports de scribed above, it has been shown that bronchoconstric tion induced by a low concentration of peptide LT (0.5 ,ug/kg) is mostly inhibited by indomethacin (24,25). On the other hand, it has been reported that broncho constriction at higher concentrations of peptide LT (> 0.8 ,ug/kg) is only partially blocked by indomethacin (18,23,26). Therefore, it is suggested that bronchocon strictions at a higher concentration of peptide LT (2 ,u g/kg) were induced by both the direct action of pep tide LT and the release of TXA2.…”
Section: Discussionmentioning
confidence: 99%